Effects of LAGP electrolyte on suppressing polysulfide shuttling in Li–S cells. Issue 62 (15th June 2016) - Wu, Xue-ling; Zong, Jun; Xu, Han; Wang, Wei; Liu, Xing-jiang
Abstract : In this work, the solid electrolyte of Li1.5 Al0.5 Ge1.5 (PO4 )3 (LAGP) is used to suppress polysulfides shuttling in Li–S cells. Abstract : In this work, the solid electrolyte of Li1.5 Al0.5 Ge1.5 (PO4 )3 (LAGP) is used to suppress polysulfides shuttling in Li–S cells. Firstly, the H-type visible cell is assembled by using a LAGP glass ceramic plate and normal poly-propylene (PP) separator. It is demonstrated that the LAGP glass ceramic plate is quite effective in shutting-down the migration of polysulfide ions and improving the utilization ratio of the sulfur cathode. However, in the commercial production of Li–S batteries it is not possible to use the LAGP glass ceramic plate as a membrane due to its brittle characteristics. Herein, the LAGP modified separator has been prepared by a simple casting procedure and applied in Li–S cells. The Li-ion conductivity of the LAGP modified separator is 6.280 × 10 −4 S cm −1 at room temperature. The Li-ion transference number and the Gurley value of the modified separator show that the diffusion of the polysulfide anions can be suppressed effectively. The discharge capacity of the Li–S cell with the modified separator at the 50th cycle can reach 770.1 mA h g −1, while that of the Li–S cell with the routine PP separator is only 658.4 mA h g −1 at the 50th cycle. The superior utilization of sulfur in the Li–S cells indicates that using the LAGP modified separator is a viable way to overcome the shuttling problem for practical Li–S batteries.